Problematika Pembelajaran Bahasa Arab di Madrasah Ibtidaiyah Swasta UMMI Lubuk Pakam - Siti Mahrami Ivlatia; Ernida Hasibuan; Siti Sa'idah (Yayasan Haiah Nusratul Islam, 2023)
Arabic is a language that every Muslim must learn. Islamic-based madrasahs make Arabic a compulsory subject. There are problems in learning Arabic in this Madrasah, namely many of the students when learning Arabic students feel bored, the assumption that Arabic is a difficult subject to learn, the lack of knowledge of mufrodat in students, and Arabic language learning that is less structured. The method used in compiling the study of this journal discussion is a qualitative method by conducting observations for research and library research sourced from books, journals and other articles as supporting references. There are internal and external factors that cause the emergence of Arabic learning problems. The internal factors are learning methods, media or facilities, student motivation, and learning resources used during the learning process. While the external factors are the environment and the absence of Madrasah programs on lesson plans. The efforts in overcoming this problem will be presented in the discussion.